2012
DOI: 10.4236/ojss.2012.23032
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic C:N vs. Water-Extractable Organic C:N

Abstract: Traditionally, soil-testing laboratories have used a variety of methods to determine soil organic matter, yet they lack a practical method to predict potential N mineralization/immobilization from soil organic matter. Soils with high micro-bial activity may experience N immobilization (or reduced net N mineralization), and this issue remains unresolved in how to predict these conditions of net mineralization or net immobilization. Prediction may become possible with the use of a more sensitive method to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 18 publications
6
79
1
Order By: Relevance
“…Haney et al [28] compared soils from the Riesel study to soils collected from agricultural fields in Idaho, Georgia, Maine, Mississippi Oklahoma, Texas, and Wyoming to understand the relationship between soil organic C:N and WEOC:WEON. They concluded that the WEOC:WEON ratio was a more sensitive measurement than total C:N because of the direct influence of soluble C and N on microbial metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Haney et al [28] compared soils from the Riesel study to soils collected from agricultural fields in Idaho, Georgia, Maine, Mississippi Oklahoma, Texas, and Wyoming to understand the relationship between soil organic C:N and WEOC:WEON. They concluded that the WEOC:WEON ratio was a more sensitive measurement than total C:N because of the direct influence of soluble C and N on microbial metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between the biology of the soil and the inorganic components of the soil are predictable and can be easily modeled using the soil test data we obtained. Haney et al (2012) found that soil microbial activity measured as the flush of 1-d CO 2 following rewetting of dried soil was significantly correlated to WEOC and WEON. Figure 3 depicts the relationships between 1-d CO 2 , WEOC and WEON values for various soils throughout the contiguous United States (data from USDA-ARS).…”
Section: Model Theorymentioning
confidence: 99%
“…Figure 3 depicts the relationships between 1-d CO 2 , WEOC and WEON values for various soils throughout the contiguous United States (data from USDA-ARS). Short-term C respiration from soil after drying and rewetting is also highly correlated with soil microbial biomass C and 24-d N mineralization (Haney et al, 2012). The laboratory Drying and Rewetting (D/R) process mimics the natural processes in the field that occur with rainfall events, the extent of which depends upon climatic and soil conditions.…”
Section: Model Theorymentioning
confidence: 99%
“…Organic matter content in the soil is closely related to soil N content. It was reported by Haney et al (2012) that the N and C-organic soil content had a close correlation (r 2 =0.93), and so did between N and the water extracted C-organic (r 2 =0.84) on farms of Idaho, Georgia, Maine, Mississippi, Oklahoma, Texas and Wyoming. N is a mobile nutrient and easily lost through evaporation, leaching and lateral flow.…”
Section: Soil Characteristic In the Experiments Sitementioning
confidence: 99%